2017
DOI: 10.3389/fneur.2017.00333
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Has Neuroprotective Potential: Focus on Parkinson’s Disease and Migraine

Abstract: With the huge negative impact of neurological disorders on patient’s life and society resources, the discovery of neuroprotective agents is critical and cost-effective. Neuroprotective agents can prevent and/or modify the course of neurological disorders. Despite being underestimated, riboflavin offers neuroprotective mechanisms. Significant pathogenesis-related mechanisms are shared by, but not restricted to, Parkinson’s disease (PD) and migraine headache. Those pathogenesis-related mechanisms can be tackled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 93 publications
(159 reference statements)
2
70
0
3
Order By: Relevance
“…FMN1 encodes an essential enzyme that is responsible for catalyzing the phosphorylation of riboflavin (vitamin B 2 ), in turn to produce the active forms of this vitamin 35 . Riboflavin has been found to act as a potential neuroprotective agent, preventing and/or modifying the process of neurological disorders by improving conditions of oxidative stress, mitochondrial dysfunction, and neuroinflammation 36 . Moreover, mRNA levels of human RFK (riboflavin kinase), the ortholog of yeast FMN1, have found to be significantly lower in the cerebellum, visual cortex and prefrontal cortex of AD patients versus controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FMN1 encodes an essential enzyme that is responsible for catalyzing the phosphorylation of riboflavin (vitamin B 2 ), in turn to produce the active forms of this vitamin 35 . Riboflavin has been found to act as a potential neuroprotective agent, preventing and/or modifying the process of neurological disorders by improving conditions of oxidative stress, mitochondrial dysfunction, and neuroinflammation 36 . Moreover, mRNA levels of human RFK (riboflavin kinase), the ortholog of yeast FMN1, have found to be significantly lower in the cerebellum, visual cortex and prefrontal cortex of AD patients versus controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…27 Symptomatic riboflavin deficiency often occurs in association with deficiencies of other vitamins and has usually been attributed to dietary restriction; however, it is potentially more widespread than currently recognised with an estimated 10% to 15% of the global population having an inherited restriction in their ability to absorb or utilise riboflavin. 3,28 Supplementation for prevention of ariboflavinosis is generally not necessary as adequate amounts of riboflavin are available in a healthy diet, except when the diet is very limited or other health issues are present. Riboflavin deficiency can, however, occur during lactation, phototherapy in infants, or as a consequence of coeliac disease, alcoholism, malignancies, or use of prescription drugs including phenothiazine-derived antipsychotic medications, the antimalarial drug quinacrine, phenobarbital and the cancer chemotherapy agent adriamycin.…”
Section: Nutritional Riboflavin Deficiencymentioning
confidence: 99%
“…87 Therefore, the reduction of Prevotellaceae and Prevotella detected in PD feces in some of the studies here examined is consistent with the already reported deficiencies in thiamine in PD patients 109,110 and with the olfactory dysfunction associated with low levels of thiamine in early stages of the disease. 111 Similarly, Bacteroides are associated with an enriched riboflavin biosynthesis, 87 which has shown potential neuroprotective effects in PD 112 given that riboflavin deficiency may cause an upregulation of PD pathways. 113…”
Section: Vitamin Biosynthesismentioning
confidence: 99%